Model Aktivitas Fisik pada Kampus Berfasilitas Minimal - Siti Fatimah (Berita Kedokteran Masyarakat (BKM), 2020)
Introduction: A high activity and lack of adequate health facilities make colleges abandon healthy lifestyle patterns. All of most colleges in Yogyakarta don't have adequate facilities to perform physical activities on campus. A model of physical activity on a college having minimal facilities is essential. It shows that a healthy lifestyle can be performed by anyone and anywhere. Goal: The purpose of this model discover an idea of physical activity on campus having less adequate facilities, especially in Poltekkes Karya Husada Yogyakarta. Method: This method uses literature study of physical activity on campus not requiring a lot of facilities. After obtaining specific samples, model is selected matching with Poltekkes Karya Husada Yogyakarta. Some models for performing healthy living on campuses with minimal facilities are walking or cycling to campus, up and down the stairs and stretching between work and college. The model becomes a recommendation of physical activities at Poltekkes Karya Husada Yogyakarta particularly and other institutions. Conclutions: Stretching between study times, going up and down the stairs and cycling to campus are activities that can be performed anywhere without requiring adequate facilities. It can result in 43 minutes of physical activity without having scheduled time. A saying “man jadda wa jada”, those who are sincere will get results. Minimum facilities in campus will not restrict us to any physical activity, if we have a strong will. Keywords: phisical activty, healthy campus, minimum facility